Extraction optimization compounds from curcuma xanthorrhiza Roxb Rhizome using Pressurized Hot Water Extraction (PHWE) - Nur Syafiqah Yusof (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Pressurized Hot Water extraction (PHWE) was implemented in attempt the use to reduce the toxic organic solvent in extracting bioactive compound from Curcuma xanthorrhiza Roxb rhizomes. The screening studies using single factorial experiment were performed prior to optimization. The optimum process parameters were determined by employing response surface methodology (RSM).The effect of temperature, extraction time and solvent volume towards total phenolic compound (TPC) were investigated. Results showed that temperature and solvent volume were the most significant (p<0.001) factor affecting the TPC. It was predicted that the optimum extraction process parameter within the experiment range would be at temperature of 155.37 C, extraction time of 45.71 min, and solvent volume of 60 mL. Under the optimized conditions, the highest value of TPC obtained was 15.961mg GAE/g dry weight which reasonably close to the predicted value of 15.143 mg GAE/g dry weight. Thus, the result showed that the second order polynomial model was significant since the data were adequately fitted into model.